Change management in e-government: OntoGov case study. (27th December 2005) - Stojanovic, Ljiljana; Stojanovic, Nenad; Apostolou, Dimitris
E-government systems are subject to a continual change. The importance of better change management is nowadays, more important due to the evolution of Europe towards a multicultural, more open and international society with changing common values, increasing levels of education, demographic involvement and adoption of new technologies. In this paper, we show how semantic technologies may improve management of changes regarding process knowledge in an e-government system. We consider change management process as a continual improvement process. To improve the usability of e-government services, we propose new methods for the semantic service annotation as well as for semantic service discovery. Particularly, we focus on new level of functionality such as verification of a service annotation and refinement of search results.